Climate Risk Country Profile : Nepal - World Bank Group; Asian Development Bank (World Bank, Washington, DC and Asian Development Bank, Manila, 2021)
Water and forests are Nepal’s most abundant natural resources, with freshwater (derived from glaciers, snowmelt, and rainfall) accounting for an estimated 2.27 percent of the total world supply. Weakness in effective response mechanisms and strategies for dealing with natural hazards has historically exacerbated this vulnerability. An increase in soil erosion, landslides, flash floods, and droughts has been reported in recent years across the country, with increased intensity and impact on the lives and livelihoods of the Nepalese. This document aims to succinctly summarize the climate risks faced by Nepal. This includes rapid onset and long-term changes in key climate parameters, as well as impacts of these changes on communities, livelihoods, and economies, many of which are already underway. This is a high-level synthesis of existing research and analyses, focusing on the geographic domain of Nepal, therefore potentially excluding some international influences and localized impacts. The core data presented is sourced from the database sitting behind the World Bank Group’s (WBG) climate change knowledge portal (CCKP), incorporating climate projections from the Coupled Model Inter-comparison Project Phase 5 (CMIP5). This document is primarily meant for WBG and Asian Development Bank (ADB) staff to inform their climate actions. The document also aims and to direct the reader to many useful sources of secondary data and research.